Abortion – Freedom of Decision or a Crime? - Latakaitė, Greta; Rimzhus, Lidiya (Vilnius University Open Series, 2024)
This article analyzes an issue that has existed for a very long time in human history but is one of the most debated worldwide. There is no consensus: abortion is a woman‘s freedom of choice, or for that matter, a crime. The work presents the beginning of human life. He explains how abortion is understood from religious, legal, and medical perspectives. The features of the crime of illegal abortion are given. In this written work, a comparative analysis of other foreign countries is also carried out, which aims to clarify the legal regulation of abortion in other countries.
Keywords: abortion; criminal offence; freedom of self-determination; The Criminal Code of the Republic of Lithuania; The Supreme Court of Lithuania